β3-Chimaerin, a novel member of the chimaerin Rac-GAP family - Zubeldia Brenner, Lautaro (2014)
Chimaerins are a family of diacylglycerol- and phorbol ester-regulated GTPase activating proteins (GAPs) for the small G-protein Rac. Extensive evidence indicates that these proteins play important roles in development, axon guidance, metabolism, cell motility, and T cell activation. Four isoforms have been reported to-date, which are products of CHN1 (α1- and α2-chimaerins) and CHN2 (β1- and β2-chimaerins) genes. Although these gene products are assumed to be generated by alternative splicing, bioinformatics analysis of the CHN2 gene revealed that β1- and β2-chimaerins are the products of alternative transcription start sites (TSSs) in different promoter regions. Furthermore, we found an additional TSS in CHN2 gene that leads to a novel product, which we named β3-chimaerin. Expression profile analysis revealed predominantly low levels for the β3-chimaerin transcript, with higher expression levels in epididymis, plasma blood leucocytes, spleen, thymus, as well as various areas of the brain. In addition to the prototypical SH2, C1, and Rac-GAP domains, β3-chimaerin has a unique N-terminal domain. Studies in cells established that β3-chimaerin has Rac-GAP activity and is responsive to phorbol esters. The enhanced responsiveness of β3-chimaerin for phorbol ester-induced translocation relative to β2-chimaerin suggests differential ligand accessibility to the C1 domain.